Yazılı basın işletmelerinde teknolojik gelişimin etkileri - Çalışkan, Aysun Şimşir (My University, 2010)
leri Teknolojiler, Teknoloji Yönetimi ÖZET YAZILI BASIN İŞLETMELERİNDE TEKNOLOJİK GELİŞİMİN ETKİLERİ İşletmelerin küreselleşen dünyada rekabet ortamlarında başarı sağlamaları ileri teknolojileri işletmelerine transfer edip üretimde bu teknolojileri kullanmalarına bağlıdır. Yazılı basın işletmeleri, ekonomik ve finansal güçlükler karşında bu olanağı yakalamak için çaba sarfetmişlerdir. Yazılı basın işletmelerinde her işletme gelişen teknolojiyi, ekonomik gücü doğrultusunda almış ve hayata geçirmiştir. Teknolojinin hayata geçirilmesi ile yazılı basın işletmeleri zamandan, maliyetten, işgücünden kazanca ulaşmış baskı kalitesini maksimum seviyeye çıkarmıştır. Yazılı basın işletmelerine yapılan teknolojik yatırım sadece gazete-reklam geliri olarak kalmamış, gazetelerin çatısı altında olduğu holdinglerin diğer yan kuruluşları içinde fayda ve kar sağlamıştır. Yazılı basın işletmeleri ileri teknolojileri kullanarak değişen koşullara uyum sağlamış ve rekabet ortamında başarılı olmuştur. II Name and Surname : Aysun Şimşir Çalışkan Field : Communication Sciences Programme : Press Economics and Management Supervisor : Professor Semra Atılgan Degree Awarded and Date : Master- June 2010 Advanced Technology,Technology Management

EFFECTS OF TECHNOLOGICAL DEVELOPMENT IN THE PRESS COMPANY Success of businesses within competition of the globalized world is due to transferring their advanced technologies into production and using this technology. Print media companies, on the face of economic and financial difficulties struggled to capture this opportunity. Every business in the print media business was taken and implemented developments in technology in the direction of their economic power. With the implementation of technology, companies gain from the time of press, cost and labor work and maximized the print quality. The outcome of the technological investments executed by print media businesses had not only been newspaper-advertising revenues and also other subsidiaries under the umbrella of the holding company has provided benefits and profits from these investments as the newspapers. By using advanced technology, print media companies adapted to changing conditions and have been successful in the competitive environment.
Keywords: Basın; Basın Ekonomisi; Teknoloji; Teknoloji Yönetimi